2022
DOI: 10.2196/37290
|View full text |Cite
|
Sign up to set email alerts
|

System Usability Scale Benchmarking for Digital Health Apps: Meta-analysis

Abstract: Background The System Usability Scale (SUS) is a widely used scale that has been used to quantify the usability of many software and hardware products. However, the SUS was not specifically designed to evaluate mobile apps, or in particular digital health apps (DHAs). Objective The aim of this study was to examine whether the widely used SUS distribution for benchmarking (mean 68, SD 12.5) can be used to reliably assess the usability of DHAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 32 publications
(37 reference statements)
3
72
0
1
Order By: Relevance
“…Participants preferred the chatbot's interface, reporting higher usability and significantly higher likelihood to recommend it as a data collection tool. The reported SUS scores for the chatbot (69.7) was higher than the average industry benchmark score of 68 (19,36). The NPS score of the chatbot (NPS = 24) was higher than the online form (NPS = 13).…”
Section: Main Findingsmentioning
confidence: 78%
“…Participants preferred the chatbot's interface, reporting higher usability and significantly higher likelihood to recommend it as a data collection tool. The reported SUS scores for the chatbot (69.7) was higher than the average industry benchmark score of 68 (19,36). The NPS score of the chatbot (NPS = 24) was higher than the online form (NPS = 13).…”
Section: Main Findingsmentioning
confidence: 78%
“…The SUS tool has been defined as technology-agnostic, suitable for all type of user interfaces, and Hyzy at al. [ 53 ] demonstrated that the use of the SUS could be reliable in case of mHealth solutions. A simplified version of the SUS was proposed by Holden [ 54 ] for cognitively impaired and older adults that could not understand all the SUS statements properly.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for these findings. Although the SUS score distribution has been used for benchmarking a vast array of new technologies and more recently shown to be suitable for benchmarking mHealth or digital health apps (excluding apps just for self-monitoring physical activity), it is possible that the benchmark score could be subject to reporting bias in the literature, that is, the file drawer problem, where researchers may be more likely to report only higher usability [ 34 , 53 ]. Low mHealth usability has been found in previous studies in vulnerable, underserved populations based on other usability scales and metrics [ 54 , 55 ]; however, to the best of our knowledge, this is the first time SUS scores have been reported for a digital health app with 2 separate interfaces for 2 types of end users, CMs and AYA living with HIV participants.…”
Section: Discussionmentioning
confidence: 99%
“…The SUS has been validated for use with mobile and web apps and scores range from 0 to 100, with higher scores indicating higher perceived usability [ 33 ]. A score >68 is considered above the industry average [ 34 ].…”
Section: Methodsmentioning
confidence: 99%